Phase II study of a weekly 24-hour infusion with 5-fluorouracil and simultaneous sodium - folinic acid in the first-line treatment of metastatic colorectal cancer - Hartung, Gernot; Hofheinz, Ralf-Dieter; Wein, A.; Riedel, C.; Rost, A.; Fritze, D.; Kreuser, Ernst-Dietrich; Drees, M.; Kühnel, J.; Hehlmann, Rüdiger; Queißer, Wolfgang (Onkologie, 2001)
Background: A weekly continuous 24-hour infusion therapy with 5-fluorouracil (5-FU) and calcium - folinic acid (CA-FA) was shown to be an effective first-line treatment in advanced metastatic colorectal cancer. Sodium - folinic acid (S-FA) is a new formulation which, in contrast to CA-FA allows the simultaneous i.v. administration in combination with 5-FU in one pump. Patients and Methods: From 1997 to 1998, 51 patients [median age 60 (range 24-77) years; 38 male, 13 female] with metastatic colorectal cancer were recruited in 5 centers to receive weekly 24-hour infusions of 5-FU (2,600 mg/m2) and S-FA (500 mg/m2) dissolved in one pump for 6 weeks as first-line treatment. The treatment cycle was repeated after a 2-week rest period. Results: 1,178 administrations (median 24, range 3-54) were performed during the study. Out of 51 patients (median follow-up 20.2 months), 2 (3.9%) achieved complete remission (CR), 17 (33.3%) partial remission (PR), and 21 (41.2%) no change (NC). Progressive disease (PD) was observed in 11/51 (21.6%) patients, including 6 patients who did not complete the first cycle. Median time to tumor progression (TTP) was 8.5 months (95% CI: 5.8-11.3). 32/51 (62.7%) patients survived for more than 1 year, the median survival was reached at 16.5 months (95%CI: 10.2-22.8). Among major toxicities, NCICTC grade III/IV diarrhea occurred in 13/51 (25.4%), grade III hand-foot syndrome in 6/51 (11.7%) patients. Grade III/IV stomatitis was observed in 4/51 (7.8%), cardiac toxicity occurred in 2/51 patients (3.9%). Conclusion: Similar to conventional 24-hour 5-FU + CA-FA treatment, the combination with S-FA induced 37.2% objective responses with moderate toxicity. However, TTP seems favorable and the administration of S-FA is convenient, while saving costs and time for the patient in outpatient units.
Gesehen am 18.05.2022